A theory of caring - Watson, Jean ([S.l. : s.n.], 1989)
In this video, Jean Watson explains her theory human caring and discusses how the metaphysical and emotional aspects of nursing related to nursing theory. The program includes a brief biographical sketch and a synopsis of Watson's ideas
The nurse theorists portraits of excellent
Keywords: Nursing Theory; Empathy